2015
DOI: 10.1155/2015/479798
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Melanocytes-Specific Cytotoxicity Induced by Phenol Compounds Having a Prooxidant Effect, relating to the Appearance of Leukoderma

Abstract: Specific phenol compounds including rhododendrol (RD), a skin-brightening ingredient in cosmetics, are reported to induce leukoderma, inducing a social problem, and the elucidation of mechanism of leukoderma is strongly demanded. This study investigated the relationship among the cytotoxicities of six phenol compounds on B16F10 melanoma cells and HaCaT keratinocytes and generated reactive oxygen species (ROS). As a result, the cytotoxicity of RD on B16F10 cells was higher than that on HaCaT cells, and RD signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…As previously reported, hydrogen peroxide is produced during tyrosinase-catalyzed rhododendrol and rhododendrol-catechol oxidations. (13) We also confirmed the hydrogen peroxide generation by measuring the increase in dissolved oxygen concentration by the addition of catalase. The hydrogen peroxide generated in the oxidation of rhododendrol and rhododendrol-catechol may cause hydroxyl radical generation.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As previously reported, hydrogen peroxide is produced during tyrosinase-catalyzed rhododendrol and rhododendrol-catechol oxidations. (13) We also confirmed the hydrogen peroxide generation by measuring the increase in dissolved oxygen concentration by the addition of catalase. The hydrogen peroxide generated in the oxidation of rhododendrol and rhododendrol-catechol may cause hydroxyl radical generation.…”
Section: Resultssupporting
confidence: 65%
“…The generation of hydroxyl radicals was observed in a mixture of rhododendrol, tyrosinase, and hydrogen peroxide, and the generation was enhanced by irradiation with 1,000 J/m 2 UV-B (ultraviolet light with 280–315 nm-wavelength). (13) Further, ROS generation was detected during rhododendrol oxidation by tyrosinase. (14) Hence, in addition to hydrogen peroxide, hydroxyl radicals and singlet oxygen ( 1 O 2 ) are strong candidates for the onset of leukoderma caused by rhododendrol.…”
Section: Introductionmentioning
confidence: 99%
“…Catalase is the main enzyme responsible for the degradation of hydrogen peroxide in melanocytes . When H 2 O 2 is not effectively eliminated, levels of reactive hydroxyl radicals may increase due to iron‐catalyzed Fenton reaction . Moreover, in pigmented cells melanin can act as a free radicals scavenger and may possess the superoxide dismutase activity …”
Section: Discussionmentioning
confidence: 99%
“…To clarify the pathogenesis of RD‐induced leukoderma, we investigated the effect of UVR in NHEMs treated with RD, as a potential additional factor enhancing RD‐induced melanocyte cytotoxicity. Recent reports indicated that UVB exposure influences RD‐induced melanocyte cytotoxicity . Nagata et al showed that UVB irradiation amplifies RD‐induced cytotoxicity in B16F10 melanoma cells and increases the generation of hydroxyl radicals by a mixture of tyrosinase and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that UVB exposure influences RD‐induced melanocyte cytotoxicity . Nagata et al showed that UVB irradiation amplifies RD‐induced cytotoxicity in B16F10 melanoma cells and increases the generation of hydroxyl radicals by a mixture of tyrosinase and H 2 O 2 . Lee et al have shown that UVB irradiation enhances RD‐induced cytotoxicity and induces apoptosis in NHEMs.…”
Section: Discussionmentioning
confidence: 99%